Physical Activity and Health - Ivan Uher; zuzana Küchelová; Iveta Cimboláková; Ján Pivovarník (Jan Długosz University in Częstochowa, 2019)
Health is a condition of complete physical, mental and social wellbeing and not merely the absence of illness or disability. Health is not something one receives but something one has to work and strive towards. This presupposes active efforts from the individual, the family, and the community. In the chain of causative factors and pathological processes which can lead to illness, disability, and death, there are many links, some known and some unknown. Our resources and means must be applied at that point in the causative chain where the best prospects lie for reducing the incidence of illness, disability, and death. Diseases due lifestyle and environmental factors now dominate our health statistics. Material standards of living and personal philosophy of life bear a close relationship to the origin and development of these diseases. In that respect, regular physical activity is seen as an essential component in a lifestyle which itself is the basis for the health promoting idea. In our review we look into physical activity and its influence on health.